2016
DOI: 10.1093/europace/euv436
|View full text |Cite
|
Sign up to set email alerts
|

Battery drain in daily practice and medium-term projections on longevity of cardioverter-defibrillators: an analysis from a remote monitoring database

Abstract: AimsThe longevity of generators is a crucial determinant of the cost-effectiveness of therapy with implantable cardioverter-defibrillators (ICDs) and cardiac resynchronization therapy defibrillators (CRT-D). We evaluated the trend of device-measured residual battery capacity and longevity projections over 5-year follow-up. We also investigated possible factors associated with battery drain.Methods and resultsData from 4851 patients in the European LATITUDE® database who were followed up for a minimum of 3 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The median pacing threshold at 3 months was 1.0 V for Spiral and 1.2 V for Straight leads. This will provide implanting physicians options to pace closer to the basal region of the left ventricle regardless of patient anatomy and will have a positive effect on CRT‐D longevity, as high LV pacing output has shown to be a strong determinant of increased battery drain and shorter times to elective replacement …”
Section: Discussionmentioning
confidence: 99%
“…The median pacing threshold at 3 months was 1.0 V for Spiral and 1.2 V for Straight leads. This will provide implanting physicians options to pace closer to the basal region of the left ventricle regardless of patient anatomy and will have a positive effect on CRT‐D longevity, as high LV pacing output has shown to be a strong determinant of increased battery drain and shorter times to elective replacement …”
Section: Discussionmentioning
confidence: 99%
“…Reducing the frequency of generator replacements would also reduce the frequency of important complications, such as device infection, and their consequent costs . Real‐life longevity is definitely sharply shorter compared with the industry‐projected longevity, which has always overestimated ICD device performance …”
Section: Discussionmentioning
confidence: 99%
“…Manufacturers of the newer‐generation ICD models promise a 5‐ to 9‐year projected longevity . There have been a few previous studies reporting on the longevity of newer ICD systems that practically refute this industry claim .…”
Section: Introductionmentioning
confidence: 99%
“…The longevity gauge has been introduced in Boston Scientific ICDs since 2008 and in Medtronic ICDs since 2013, but we did not have enough numbers of patients at our institution whose devices reached ERI to make a meaningful comparison. One study of Boston Scientific devices based on a remote monitoring database reported that the estimated longevity of CRT‐ICDs exceeded 10 years, but these devices were still in service at the end of that study, and it remains to be seen if there is any discrepancy between actual and estimated longevity …”
Section: Discussionmentioning
confidence: 99%